Aplikasi Media Pembelajaran Untuk Anak Usia Dini Guna Mengenalkan Jiwa Patriotisme - Hala Nuari Lina Darmawati; Nia Saurina (Informatics Engineering Department-UWKS, 2021)
Patriotism is a doctrine which teaches us to love the homeland. Early childhood education is one form of education that focuses on the implementation of the foundation in the direction of growth, early childhood education, where education before primary education which is a development effort aimed at children from birth to the age of six years. The importance of foster patriotism should start from an early age. Lack of knowledge about the history of the child makes the child does not know the ideals of this nation. And media that are less attractive as heroic, making an early age children are hungry for knowledge of history and reluctant to learn history. For the early childhood program requires effective and efficient aid, which has a lot of funny pictures and can attract the attention of the child to interact directly. In connection with the following, can be given a solution with application made this early childhood. This application is an instructional media to learn about the hero who will get to know the child will diituntun patriotism by playing puzzle that compose heroes scrambled picture and listening histories of heroes who have high patriotism. Adding insight to learn about the history of the exercises. So with the application of these media can help the learning process fun, creative, and do not bore children at an early age to be more passion in studying the history of Indonesia.